A divergent strategy for the synthesis of redox-active verdazyl radical polymers. Issue 18 (21st April 2021) - Magnan, François; Dhindsa, Jasveer S.; Anghel, Michael; Bazylewski, Paul; Fanchini, Giovanni; Gilroy, Joe B.
Abstract : We describe a divergent synthetic strategy based on ATRP and CuAAC chemistry for the production of stable radical polymers. As a proof of concept, we prepare verdazyl radical polymers with properties suitable for use in organic electronics. Abstract : Stable radical polymers have attracted significant attention due to their use as magnetic materials, (co)catalysts in organic synthesis, and as functional components of organic electronics including batteries and memory devices. Despite their importance, a relatively narrow range of synthetic strategies exist for their production. The most common examples involve the transition-metal catalyzed polymerization of radical-containing monomers or the sequential polymerization of monomers containing radical precursors and their post-polymerization conversion to radicals. Post-polymerization installation of stable radicals is not commonly reported. Copper-assisted azide-alkyne cycloaddition (CuAAC) chemistry has seen limited use in this regard, but only for the production of π-conjugated and particle-bound polymers. Here, we present a divergent synthetic strategy for the production of stable radical polymers, that takes advantage of the efficiency of atom transfer radical polymerization and CuAAC chemistry, and is anticipated as general to a wide range of stable radicals. We chose verdazyl radicals as a case study for this synthetic paradigm as they offer highly tunable properties based on minor structural changes, and thus well represent the need for the divergent synthetic strategy presented.